PROMOTING ENVIRONMENTAL AWARENESS IN LEARNING CONTEXTS - Dirtya S. Paradewari; Anchieta A. Avillanova; Aloysia B. Lasar (Sanata Dharma University, 2018)
A bundle of studies in multidisciplinary context has been conducted concerningthe earth changes. As we are now witnessing the destruction that our earth issuffering from, promoting environmental awareness becomes visible to be vital.In line with the rapid development of information mobility and technology,English is becoming worlds language. The scope of English users then proved tobe continuously in growth. Therefore, English as foreign language (EFL) learningcontext is considered ideal to promote the environmental awareness. There are some evidence that support the way of promoting the environmental awareness inthe educational context. Moreover, Pike and Shelby (1994) point outconsciousness in various aspects as the desired result for promoting environmentalawareness through education. This paper elaborates those evidence and discussesthe aims of global environmental education.